PSA and androgen-related gene (AR, CYP17, and CYP19) polymorphisms and the risk of adenocarcinoma at prostate biopsy - dos Santos, Rodrigo Mattos [UNESP]; Jesus, Carlos Marcio Nobrega de [UNESP]; Souza Trindade Filho, Jose Carlos; Souza Trindade, Jose Carlos; Camargo, João Lauro Viana de [UNESP]; Rainho, Claudia Aparecida [UNESP]; Rogatto, Silvia Regina [UNESP] (Mary Ann Liebert, Inc., 2008)
The aim of the present study was to examine the impact of polymorphisms in prostate-specific antigen (PSA) and androgen-related genes (AR, CYP17, and CYP19) on prostate cancer (PCa) risk in selected high-risk patients who underwent prostate biopsy. Blood samples and prostate tissues were obtained for DNA analysis. Single-nucleotide polymorphisms in the 50-untranslated regions (UTRs) of the PSA (substitution A > G at position -158) and CYP17 (substitution T > C at 50-UTR) genes were detected by polymerase chain reaction (PCR)-restriction fragment length polymorphism assays. The CAG and TTTA repeats in the AR and CYP19 genes, respectively, were genotyped by PCR-based GeneScan analysis. Patients with the GG genotype of the PSA gene had a higher risk of PCa than those with the AG or AA genotype (OR = 3.79, p = 0.00138). The AA genotype was associated with lower PSA levels (6.44 +/- 1.64 ng/mL) compared with genotypes having at least one G allele (10.44 +/- 10.06 ng/mL) (p = 0.0687, 95% CI - 0.3146 to 8.315, unpaired t-test). The multivariate analysis confirmed the association between PSA levels and PSA genotypes (AA vs. AG+GG; chi(2) = 0.0482) and CYP19 (short alleles homozygous vs. at least one long allele; chi(2) = 0.0110) genotypes. Genetic instability at the AR locus leading to somatic mosaicism was detected in one PCa patient by comparing the length of AR CAG repeats in matched peripheral blood and prostate biopsy cores. Taken together, these findings suggest that the PSA genotype should be a clinically relevant biomarker to predict the PCa risk.